Impact of Varying Amplitudes of Upward and Downward Motion on the Torque/Force Generation, Canal-Centering Ability, and Cyclic Fatigue Resistance of Nickel–Titanium Reciprocating Instrument - Keiko Hirano; Shunsuke Kimura; Keiichiro Maki; Satoshi Omori; Arata Ebihara; Takashi Okiji (Applied Sciences)
The optimal amplitude of pecking motion during nickel–titanium rotary root canal instrumentation remains unclear. This study evaluated how different pecking amplitudes influence the force/torque generation, canal-centering ability, and cyclic fatigue resistance of the Reciproc Blue R25 instrument. Thirty J-shaped resin canals were instrumented with Reciproc Blue using automated instrumentation and a torque/force sensing device with an up-and-down speed of 50 mm/min and varying pecking amplitudes: Group S (1 s apically, 0.5 s coronally), Group M (2 s apically, 1 s coronally), and Group L (4 s apically, 2 s coronally) (n = 10 each). Force/torque were recorded, and canal-centering ratios were determined. In a dynamic cyclic fatigue test, the Reciproc Blue instruments were rotated in a curved metal canal with 1 mm or 3 mm back-and-forth motions (n = 10 each). Group L exhibited significantly greater maximum downward force and cumulative upward (screw-in) force than Group S (p < 0.05), but torque was not significantly different across groups. Groups M and L exhibited a significantly smaller canal-centering ratio than Group S (p < 0.05). Pecking at 3 mm led to a significantly longer time to fracture and shorter fragment lengths than 1 mm pecking (p < 0.05). In the Reciproc Blue instrumentation, higher pecking amplitude improved canal-centering ability and cyclic fatigue resistance while increasing upward and downward forces.